Cebrayil-Büyük Mercanlı Çevresi Bayatıları Turkish Poems of Gebrail-Large Mardzhanly Surroundings - KEMALOĞLU, MUHAMMET (Journal of History Culture and Art Research, 2014)
Cebrayil, Azerbaycan'daki merkezi şehirlerinden biridir. 1993'ten bu yana Ermenistan Silahlı Kuvvetleri'nin işgali altındadır. Cebrayil ili ve özellikle Büyük Mercanlı çevresinde Terekeme ve Karapapah Türklerinin meydana gelen sosyal ve kültürel olayların birçoğunda kendi karakteristik özelliklerini yansıttığını göstermiştir. Bu çalışmamızda Büyük Mercanlı Terekeme ve Karapapah Türklerinin bayatıları ele alınmıştır. AbstractGabriel is one of the central cities of Azerbaijan. It has been under occupation by the Armenian Armed Forces since 1993. Terekeme and Karapapakh Turks have reflected their own characteristics in many of the social and cultural events in Gabriel Province, especially around Large Mardzhanly. In this study, Turkish poems of Large Mardzhanly Terekeme and Karapapakh Turks have been studied.